POLA MIKROBA SENSITIVITAS ANTIBIOTIK DAN KELUARAN JANGKA PENDEK ABSES SEREBRI DI RSUPN CIPTO MANGUNKUSUMO - Donna Octaviani, Nurul Komari, Riwanti Estiasari, Darma Imran, Ratna D. Restuti, Yeva Rosana, M. Sae (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION IN GENERAL THE MANAGEMENT OF CEREBRAL ABSCESS IS COMBINATION OF ANTIBIOTICS AND OPERATIVE EMPIRICAL THERAPY OF ANTIBIOTICS NEED EPIDEMIOLOGY DATA OF THE MOST COMMON CEREBRAL ABSCESS MICROBES ISOLATION TECHNIC IMPROVEMENT HAS FACILITATED THE IDENTIFICATION OF MICROBES EASILY TO INCREASE THE RECOVERY RATE AND TO DECREASE THE MORTALITY RATE